Perancangan Taman Urban Farming Berbasis Partisipasi Warga Untuk Mendukung Kemandirian Pangan Di Komplek Batara Indah 1 - Zadha Faedhillah Rana; Deki Tasima (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Public facility parks in residential areas are often left as passive spaces, even though they hold real potential for supporting social interaction, environmental quality, and household food security. This community service project aimed to develop a participatory urban farming design for the public park facility at the Batara Indah 1 Housing Complex in Pontianak City, intended as a practical guide for community-led, phased implementation. The approach was participatory design combining site observation, documentation, basic measurements, interviews, community discussions, spatial needs analysis, design development, and dissemination. Results show that the park can serve as both a productive and social space through clear zoning, accessible circulation paths, planting beds, a pergola or hydroponic area, seating, and a green buffer zone. The design helps residents understand each spatial element and set implementation priorities, while preserving the park's character as a shared public facility